Una aproximación al estudio del outsourcing de sistemas de información desde un enfoque político - Álvarez Suescun, Emilio (Cuadernos de Estudios Empresariales, 2006)
Information systems outsourcing has been mainly studied from an efficiency approach, without taking into account those political processes that underlie any organizational decision. This paper intends to better understand the role that political influences and pressures, both internal and external, play into information systems function sourcing decisions by applying the insights stemming from organization theory. In addition to developing a theoretical framework, the results of a preliminary empirical work among large Spanish firms are presented, showing the effect that interdepartmental power and isomorphism have on the decision of implementing a human resource information system.